Archaeological remains in Kashmir - Koul, Anand (Gurugram Shubhi, 2021)
The author is a well respected name as a writer on the Antiquities on Kashmir. The knowledge of Kashmir$1 (Bs early history is derived from the writing of Greek & Chinese writers. Kashmir remains indebted to the devoted labor of men such as General Cunningham, Sir Aurel Stein, Sir Walter Lawrence & Sir Francis Younghusband to name the few. At the same time it is remarkable that Kashmir produced many indigenous writers as the immortal Kalhana and Lalleswari in its own soil. The Archaeological Remains in Kashmir may not be an exhaustive book on the archaeology of Kashmir, but it is a book which is interesting and instructive. The author has visited these monuments one by one and has narrated in detail its history, legend and traditions. This book will be of great importance to the students of archaeology and architecture and will be a ready reckoner for the tourists who are always enchanted with the beauty of Kashmir.s
Keywords: India-Jammu and Kashmir; Hindu temples